2013
DOI: 10.1021/la404108v
|View full text |Cite
|
Sign up to set email alerts
|

Shape, Shell, and Vacuole Formation during the Drying of a Single Concentrated Whey Protein Droplet

Abstract: The drying of milk concentrate droplets usually leads to specific particle morphology influencing their properties and their functionality. Understanding how the final shape of the particle is formed therefore represents a key issue for industrial applications. In this study, a new approach to the investigation of droplet-particle conversion is proposed. A single droplet of concentrated globular proteins extracted from milk was deposited onto a hydrophobic substrate and placed in a dry environment. Complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 57 publications
6
44
0
Order By: Relevance
“…At Stage 3, the profile of the caseins droplet seemed not to evolve further: constant shape indicators were measured whereas the pure water droplet evaporated rapidly. Such droplet dynamics were previously observed during the drying of whey proteins (Sadek et al, 2013), which showed three similar phases corresponding to evaporation of the free water at the surface, buckling instability and in that case solidification into a spherical particle. However, the occurrence of a second phase of surface instability in the drying of caseins at t I clearly distinguished the behaviour of these two milk proteins.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…At Stage 3, the profile of the caseins droplet seemed not to evolve further: constant shape indicators were measured whereas the pure water droplet evaporated rapidly. Such droplet dynamics were previously observed during the drying of whey proteins (Sadek et al, 2013), which showed three similar phases corresponding to evaporation of the free water at the surface, buckling instability and in that case solidification into a spherical particle. However, the occurrence of a second phase of surface instability in the drying of caseins at t I clearly distinguished the behaviour of these two milk proteins.…”
Section: Resultssupporting
confidence: 71%
“…A droplet of 0.48 mg was formed with a micro-syringe (0.5 mL syringe, SGE Analytical Science) and deposited onto a hydrophobic substrate made of cylindrical pillars and described in Sadek et al (2013) (Fig. 1a,b).…”
Section: Hydrophobic Substrate and Drying Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the chemical and physical properties of the solute and the external conditions, later on different surface instabilities occur such as buckling, invagination, delamination and cracks [25]. Sadek et al [26][27][28] investigated on the drying dynamics of pendant droplets made of the two main milk proteins, whey proteins and casein micelles. For that purpose, the concentrated protein solution drop was hanged to a micropatterned substrate and exposed to stressful conditions (relative humidity, RH, below 5%).…”
Section: Single Droplet Studies Of Dairy Particle Formationmentioning
confidence: 99%
“…For example, certain solids undergo crystallization during particle formation, 36,37 and solutes that form a rigid non-shrinkable shell could produce dry particles with an internal vacuole. 10,38 During drying of the RS/silica composite droplets, an insoluble incipient shell consisting of both constitutes with dominating RS is produced by all compositions. Evaluating the chemical structure and properties of each constitute, we propose the following mechanism for the formation of the insoluble complex.…”
Section: Discussionmentioning
confidence: 99%